Identification of Phytochemical from Seaweed Extracts ( Eucheuma cottonii., Gracilaria sp., and Gelidium sp. ) Using Microwave-Assisted Extraction (MAE) - Sheravina, Tata Machreta; Rosida, Dedin Finatsiyatul; Priyanto, Anugerah Dany (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study looks at the chemical profiles of three types of red seaweed—Eucheuma cottonii, Gracilaria sp., and Gelidium sp.—using a method called microwave-assisted extraction (MAE) with a mix of ethanol and water for 7, 8, and 9 minutes. Qualitative screening was performed for seven secondary metabolites: alkaloids, flavonoids, phenols, tannins, saponins, triterpenoids, and steroids. The results showed that flavonoids and phenolic compounds were found in all the seaweed samples, but saponins were only found in the Gelidium sp. extracts. In contrast, alkaloids, tannins, triterpenoids, and steroids were not detected in any seaweed species. Phenolic compounds exhibited the highest positive intensity, while the flavonoid content appeared relatively low. Solvent composition and extraction duration influenced the extraction efficiency of the MAE method for bioactive compounds. These findings provide a valuable basis for future studies on the potential bioactivities of red seaweeds as natural sources in functional food and pharmaceutical applications. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water